Carrier multiplication perovskite solar cells - Wang, Yue (Nanyang Technological University, 2024)
Carrier multiplication (CM) is the process of converting a photon with an energy several times that of the material's bandgap (Eg) into multiple excitons. It is considered one of the most viable methods for solar cells to surpass the 33% Shockley-Queisser (SQ) limit. Theoretically, CM permits a solar cell to achieve a 44.4% maximal efficiency. Organic-inorganic halide perovskites (OIHP) emerge as a prospective material system for the realization of CM-based solar cells on account of their tuneable bandgap, slow hot carrier cooling properties highly favourable for CM, low CM threshold, and high solar cell efficiency. However, till now, CM in a real-world PSC device has not yet been demonstrated. This thesis intends to study questions on (i) whether CM would manifest in an actual PSC device operating under solar illumination; and (ii) whether it could contribute to performance enhancements. We investigate the CM behaviour in lead-tin (Pb-Sn) mixed perovskite thin films and PSCs, disclosing an effective CM in Pb-Sn mixed perovskite films and presenting the first demonstration of CM in Pb-Sn mixed PSCs. These findings are indispensable for the development of next-generation CM PSCs to exceed the SQ limit.